Stormwater quality performance using bioretention system: a preliminary study / Norshafa Elyza Muha and Lariyah Mohd Sidek - Muha, Norshafa Elyza; Mohd Sidek, Lariyah (Universiti Teknologi MARA, Perlis, 2016)
Bioretention system, also known as rain garden is a new technology for urban stormwater management that was introduced in Urban Storm Water Management Manual for Malaysia (MSMA). In Malaysia, the application of bioretention system is recommended; however there are no performance data available for field scale installations. Two pilot projects at Humid Tropics Centre (HTC), Kuala Lumpur and UNITEN, Putrajaya Campus are models of lot-scale application in Malaysia. Water quality analysis was done to determine water quality level after it has flowed through the bioretention systems. Grab samples were collected during storms at inlets and outlets and were sent to a analytical laboratory for water quality analysis to be performed. Result from analysis showed that the water tested nearly reached Water Quality Index’s Class I and Class II level of classification. Further monitoring and analysis will be made to observe the continuing performance and behavior of the system in the conditions typically found in Malaysia